2016
DOI: 10.1371/journal.pone.0156511
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Neutrophil-to-Lymphocyte Ratio with Lung Function and Exacerbations in Patients with Chronic Obstructive Pulmonary Disease

Abstract: BackgroundThe ratio of neutrophils to lymphocytes (NLR) is a widely available marker of inflammation. Several types of inflammatory cells and mediators have been found to be involved in the progression of chronic obstructive pulmonary disease (COPD). We sought to evaluate the association of the NLR with severity of airflow limitation and disease exacerbations in a COPD population.MethodsWe analyzed 885 patients from the Korean COPD Subtype Study cohort that recruited subjects with COPD from 44 referral hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
5
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 29 publications
(35 reference statements)
8
79
5
3
Order By: Relevance
“…The authors evidenced that tricuspid atrial conduction time was significantly longer in COPD patients than in controls (26.4±11.4 ms versus 17.7±7.7 ms), and a significant positive correlation was identified between tricuspid atrial conduction time and NLR (r=0.38, p<0.001). These findings, as opposed to those of LEE et al [38], which suggest that specific comorbidities can influence the kinetics of NLR.…”
Section: Nlr In Patients With Copd and Other Comorbiditiescontrasting
confidence: 99%
“…The authors evidenced that tricuspid atrial conduction time was significantly longer in COPD patients than in controls (26.4±11.4 ms versus 17.7±7.7 ms), and a significant positive correlation was identified between tricuspid atrial conduction time and NLR (r=0.38, p<0.001). These findings, as opposed to those of LEE et al [38], which suggest that specific comorbidities can influence the kinetics of NLR.…”
Section: Nlr In Patients With Copd and Other Comorbiditiescontrasting
confidence: 99%
“…NLR has been shown to be an independent prognostic factor in several types of tumours, including colorectal, lung, breast, pancreatic, gastric and ovarian cancer . Studies have also shown a correlation between the NLR and the prognosis and severity of the clinical course in pulmonary diseases such as chronic obstructive pulmonary disease, acute respiratory distress syndrome, community‐acquired pneumonia and sarcoidosis and tuberculosis . In this study, NLR has been found to be statistically significantly higher in silicosis patients with profusion categories 2 and 3 when compared to the control group.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies suggested that NLR (examining together the influences of neutrophilia and lymphopenia) reflected systemic inflammatory status in COPD, which was one of the independent predictors of future exacerbations 24,25. However, we found that NLR did not associate with FE in COPD in our study.…”
Section: Discussioncontrasting
confidence: 94%